Developing appropriate business model for maize shelling technologies in small holder farmers in North West Ethiopian Districts. Issue 1 (31st December 2023) - Gebeyehu, Sisay Geremew
Abstract: The aim of this paper is to identify and select an appropriate business model for the utilization of maize shelling technologies in small-scale farming practices. Though a very old practice, agriculture is still the central activity of the entire globe due the reason that it directly or indirectly affects the livelihood of the inhabitants. West Gojjam zone of the Amhara National Regional State (ANRS) in Ethiopia is among the known maize producing zones in Country for both consumption and as a cash crop. But, the problem is the high wastage of production due to post-harvest losses (PHL) due to mechanical shelling practices. Aiming to solve this PHL of maize production, at the shelling stage, assessments and discussion with the maize growing farmers and experts concerned were conducted. This paper tries to present an appropriate business model for enabling local small holder farmers get access to different maize shelling technologies. The research follows a survey-type design which provides both a quantitative and a qualitative description of operational and business variables, attitudes, or opinions of a population in the target area, and overall insight of the technology market. The current data shows that rental maize shelling service is feasible for the fragmented maize production of the West Gojjam zone, in the Amhara National Regional State of Ethiopia. Hence, a generic conceptual model has been developed based on the feedbacks of local smallholder farmers, agricultural agents, service providers and suppliers. This model shows how to select and make available appropriate maize shelling technologies that will fit the actual demand at household level. It also shows a rent-to-own approach of maize shelling service that will help the unemployed youth in the localities.